Processed line aerogravity data over the Recovery Lakes region and interior Dronning Maud Land, East Antarctica (2013) - Olesen, Arne; Ferraccioli, Fausto; Forsberg, René; Jordan, Tom; Matsuoka, Kenichi; Zakrajsek, Andrés; Ghidella, Marta (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Long-range airborne geophysical measurements were carried out in the ICEGRAV campaigns (2010-2013), covering hitherto unexplored parts of interior East Antarctica and part of the Antarctic Peninsula. The airborne surveys provided a regional coverage of gravity, magnetic and ice-penetrating radar measurements for major Dronning Maud Land ice stream systems, from the grounding lines up to the Recovery Lakes drainage basin, and filled in major data voids in Antarctic data compilations.We present here the processed line aerogravity data collected using a LaCoste & Romberg air-sea gravity meter S83 mounted in the BAS aerogeophysically equipped Twin Otter aircraft. Data are provided as XYZ ASCII line data. : The dataset available here includes all channels from raw through to filtered and upward continued free air anomalies. Only line sections with usable data are presented in the line by line database. Raw data from L&R meter #S83 includes: Channel names in brackets Spring tension (ST) meter units Cross coupling (CC) meter units Raw beam position (RB) mV Cross axis accelerometer output (XACC) mV Long Axis accelerometer output (LACC) mV Gravity processing steps were as follows: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 40 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = ((ST_real+CC)*0.9966)+(Beam_velocity*k_fac), k_fac=60/2.04, meter scale value =0.9966. Still readings are in mGal (Still), and were calculated assuming a linear best fit to the drift of the airborne meter observed at the start and end of every flight. Tie absolute gravity values for the survey (Base) were derived from land gravity measurements adjacent to the survey aircraft tied back to the gravity base station at Rothera Research Station. Airborne absolute gravity values (Abs_grav) = Rec_grav- Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984) Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Final free air data (FAA_clip) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Note no levelling has been applied to the free air gravity data. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1:12 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction (mGal) EotvosCor Eotvos correction (mGal) LatCor Latitude correction (mGal) FaCor Free air correction (mGal) HaccCor Horizontal acceleration correction (mGal) Free air Channels Free_air Un-filtered free air anomaly (mGal) FAA_clip Filtered free air anomaly masked (mGal) *Projected coordinates (x and y) are in Weddell Lambert with two standard parallels defined as follows: Latitude of false origin: -80 Longitude of false origin: -81 Latitude of 1st standard parallel -82 Latitude of 2nd standard parallel -78 False easting 26501 False northing 1977093